Primary Hyperparathyroidism: Diagnostic, Imaging, and Laboratory Perspectives - Qasem, Mohammed Abdullah; Riyad Ibrahim Ali Zaidan; Ali Ahmed Mohammed Alsharif; Mohammed Saleh Saeed Alsufyani; Mohammad Olayan Alenezi; Fuad Hamdan Alsahafe; Alboqami, Abdullah Muslat Dohim; Yahya Mousa Mohammed Sulayyi; Alshammari Abdullatif Habbas; Sami Hammead Alonazi (Saudi Journal of Medicine and Public Health, 2025)
<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Background:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Primary hyperparathyroidism (PHPT) is a common endocrine disorder characterized by autonomous overproduction of parathyroid hormone (PTH), leading to hypercalcemia and an increased risk of renal and skeletal complications. Historically a symptomatic disease, most cases are now detected incidentally via routine biochemical screening, presenting a shift towards asymptomatic or mild presentations. However, untreated PHPT can still lead to significant morbidity, including nephrolithiasis, osteoporosis, and neuropsychiatric symptoms. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Aim:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> This article provides a comprehensive review of PHPT from diagnostic, imaging, and laboratory perspectives, detailing its pathophysiology, clinical evaluation, and contemporary management strategies. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Methods:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> A narrative synthesis of current literature and clinical guidelines is presented, covering the etiology, epidemiology, diagnostic workup (including biochemical assays and imaging modalities), and treatment options for PHPT. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Results:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Diagnosis is confirmed by concurrent hypercalcemia and inappropriately elevated PTH levels, after excluding secondary causes and familial hypocalciuric hypercalcemia. Localization studies like ultrasound and sestamibi scans are reserved for preoperative planning. Management is individualized: parathyroidectomy is the only curative treatment and is recommended for symptomatic patients or those meeting specific criteria (e.g., age <50, osteoporosis, renal stones). For asymptomatic patients not meeting surgical criteria, a strategy of monitoring with regular calcium, renal function, and bone density checks is appropriate. Medical therapies like bisphosphonates, denosumab, and cinacalcet can help manage bone loss and hypercalcemia in non-surgical candidates. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Conclusion:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> PHPT requires a tailored approach based on symptom status, biochemical severity, and end-organ involvement. A multidisciplinary team is essential for accurate diagnosis, appropriate selection of surgical candidates, and effective long-term management to prevent complications.